Uji Aktivitas Antinosiseptik dan Analgetik Kombinasi Ekstrak Etanol Rumput Teki (Cyperus Rotundus L.) dan Ekstrak Etanol Daun Tapak Liman (Elephantopus Scaber L.) pada Mencit Putih Galur Swiss: Antinosiseptik dan Analgetik Ekstrak Etanol Rumput Teki dan Daun Tapak Liman - Poppy Diah Palupi; Karol Giovani Battista Leki (Jurnal Farmasi & Sains Indonesia, 2025)
Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. Medicinal plants have been increasingly explored as alternative analgesic agents due to their bioactive compounds. Cyperus rotundus L. contains flavonoids reported to possess analgesic properties, while Elephantopus scaber L. has traditionally been used for pain relief. This study aimed to evaluate the analgesic and antinociceptive activities of a combined ethanolic extract of Cyperus rotundus and Elephantopus scaber in male Swiss mice. This experimental laboratory study involved 10 groups of male Swiss mice (n=5 per group). Analgesic activity was assessed using the tail-flick test, while antinociceptive activity was evaluated using the hot plate test. Negative controls received CMC-Na 0.5% but were exposed to nociceptive stimuli. Positive controls received mefenamic acid (500 mg/kg BW) for analgesic testing and tramadol (50 mg/kg BW) for antinociceptive testing. Treatment groups received combined ethanolic extracts (ERTDTL) at doses of 700/400, 900/600, and 1100/800 mg/kg BW. Pain response latency was recorded 30 minutes after treatment. Data were analyzed using one-way ANOVA followed by the Dunnett post hoc test. The combined extract demonstrated significant analgesic and antinociceptive effects at all tested doses in mice subjected to thermal nociceptive stimuli. These findings suggest that the combination of extracts from Cyperus rotundus and Elephantopus scaber has potential as a natural analgesic agent.